Implementing Education for Sustainable Development in Higher Education: Case Study of Albukhary International University, Malaysia - Gapor, SA; Abd Aziz, A; Razak, DA; Sanusi, ZA (Palgrave, 2024)
Indexed by WOS/SCOPUS